Cytotoxicity and antioxidant activity of new biologically active constituents from Micromeria nervosa grown in Egypt - Mohammed F. Abdelwahab; Mohammed H. Hussein; Hazem H. Kadry (Faculty of Pharmacy, Cairo University, 2015)
Chromatographic fractionation of the acetone extract of Micromeria nervosa, resulted in the isolation and identification of new natural furanosesquiterpene alcohol; micromeriol (1), a known sterol; β-sitosterol (2), a new natural 5-β-cholestane type; nervosane (3), two known triterpenic acids; oleanolic acid (4), and ursolic acid (5). The cytotoxicity and the antioxidant activities of the acetone extract and the isolated pure compounds (1-5) were determined.